The globalization of world politics : an introduction to international relations - Baylis, John, 1946- (Oxford University Press, 2011)
The Globalization of World Politics is the complete introduction to International Relations, supporting over 300,000 students taking their first steps in IR and beyond. The sixth edition features more international case studies and a new chapter on 'Rising powers and the emerging global order'